2014
DOI: 10.1002/j.1556-6676.2014.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Working With Clients Who Self‐Injure: A Grounded Theory Approach

Abstract: This article presents the findings of a qualitative study examining the experiences of counselors in their work with clients who self‐injure. Using grounded theory methodology, the authors established 6 categories to explain the counselors’ conceptualization of self‐injury and their process of working with these clients: (a) external factors to self‐injury, (b) defining self‐injury, (c) potential for harm, (d) conditions for treatment, (e) counselors’ reactions to working with clients who self‐injure, and (f) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Finding ways to cultivate various types of supportive relationships may be an important protective factor for those who self-injure [ 17 , 18 ]. Whisenhunt et al [ 38 ] and Buser et al [ 39 ] determined that social support was necessary in decreasing or extinguishing NSSI behavior. In particular, the results of this current study indicated that those who currently self-injure perceived less support from family and significant others than both other groups, and less peer support than those who never self-injured.…”
Section: Discussionmentioning
confidence: 99%
“…Finding ways to cultivate various types of supportive relationships may be an important protective factor for those who self-injure [ 17 , 18 ]. Whisenhunt et al [ 38 ] and Buser et al [ 39 ] determined that social support was necessary in decreasing or extinguishing NSSI behavior. In particular, the results of this current study indicated that those who currently self-injure perceived less support from family and significant others than both other groups, and less peer support than those who never self-injured.…”
Section: Discussionmentioning
confidence: 99%
“…We conceived of dance as a powerful conduit for invoking and presenting the subjective experience of self-injury; a sensitive, stigmatised and under-researched topic (Whisenhunt et al, 2014). The kinaesthetic and affective nature of dance was also perceived to resonate with the physical and sensory aspect of self-injury.…”
Section: The Dance Pieces: Integrating Our Bodies Into Knowingmentioning
confidence: 99%
“…This ‘badness’ is often a general sense that self-harm is unhealthy, but there is also a sense in much of the literature 4 that there is something fundamentally ‘wrong’ with self-harm. It is variously described as ‘disturbing’ (Feldman, 1988: 252; LeCloux, 2013: 324), ‘maladaptive’ (Lewis et al., 2011: 553), ‘disfiguring and can be repulsive to counsellors’ (Whisenhunt et al., 2014: 392), ‘frightening’ (Whisenhunt et al., 2014: 392), a ‘problem behaviour’ (Bakken and Gunter, 2012: 342), and a ‘truly gruesome behaviour’ (Levenkron, 1998: 22). In the wider culture, self-harm is also regarded as disgusting, disturbing, and socially inappropriate; many individuals who engage in self-harm practices, including myself, can testify to that.…”
Section: Introductionmentioning
confidence: 99%
“…But my issue is that the ‘reasons for’ self-harm are often obscured by the insistence on seeing self-harm as a pathological act. This narrowed focus leads to responses such as a demand by clinicians that individuals ‘contract’ to cease self-harm before any kind of treatment will occur – even if the individual did not seek treatment for the self-harm but something that the self-harm is merely a symptom of – and will threaten to terminate such ‘treatment’ if said contract is ‘broken’ (see Favazza, 2011: 267; Strong, 2005: 171–172; Whisenhunt et al., 2014). Alternatively, it leads to responses such as the refusal to provide medical treatment for self-harm wounds, or treatment that would be unacceptable for any other injury – being stapled or stitched up without anaesthesia, for example, as I have been (see also Pembroke, 2004: 30) – or being refused psychiatric help when requested or even required (Pembroke, 2004: 30).…”
Section: Introductionmentioning
confidence: 99%